2022
DOI: 10.1039/d1tc04743d
|View full text |Cite
|
Sign up to set email alerts
|

Compositional optimization of mixed cation Dion–Jacobson perovskites for efficient green light emission

Abstract: The use of mixed spacer cations in quasi-2D Dion–Jacobson perovskites results in changes in film phase composition and efficient funneling for optimal composition. Optimal composition devices achieve a maximum EQE of 12.85% with TPPO passivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…S6, ESI †). It is known that the exposure to moisture 47 or solvent vapor 48 can induce re-crystallization in halide perovskites, and this could explain an initial increase in the HDASnBr 4 content in samples with TEOS. From the obtained results, it appears that ambient humidity plays a key role in the evolution of the optical properties and structure of HDASnBr 4 films.…”
Section: Resultsmentioning
confidence: 99%
“…S6, ESI †). It is known that the exposure to moisture 47 or solvent vapor 48 can induce re-crystallization in halide perovskites, and this could explain an initial increase in the HDASnBr 4 content in samples with TEOS. From the obtained results, it appears that ambient humidity plays a key role in the evolution of the optical properties and structure of HDASnBr 4 films.…”
Section: Resultsmentioning
confidence: 99%
“…Qin et al have used the mixture of two different divalent spacers 1,6-hexanediammonium (HDA) and 1,10-decanediammnoium (DDA) to fabricate green PeLEDs with EQE approaching 12.85% with an operational lifetime of 70 min. They concluded that the addition of an appropriate amount of DDA spacer with HDA at the A site cation not only improves the perovskite morphology but also prominently can generate the intermediate n = 2 and n = 3 phases in the energy landscape, which were absent from HAD-only perovskites, and facilitate the energy funneling toward low band-gap phases . Also, Shang et al have utilized the first-principle density functional theory (DFT) calculations and revealed that the dissociation energy of D-J phase perovskites consisting of divalent spacers is comparatively higher than that of the conventional R-P phase layered perovskites that consist of a monovalent organic spacer.…”
Section: Strategies To Address the Challengesmentioning
confidence: 99%
“…min. They concluded that the addition of an appropriate amount of DDA spacer with HDA at the A site cation not only improves the perovskite morphology but also prominently can generate the intermediate n = 2 and n = 3 phases in the energy landscape, which were absent from HAD-only perovskites, and facilitate the energy funneling toward low band-gap phases 69. Also, Shang et al have utilized the first-principle density functional theory (DFT) calculations and revealed that the dissociation energy of D-J 2 (Cs) n−1 Pb n Br 3n+1 perovskite composition.…”
mentioning
confidence: 99%
“…However, progress in their LED applications has been slower compared to solar cells, which is not entirely unexpected since these materials are more recent, and their efficiency still lags behind record results of RP perovskite LEDs. Nevertheless, DJ perovskite LEDs emitting in near-infrared (NIR), ,, green, ,, and blue , spectral ranges have been reported, with reported efficiencies in the blue spectral range of 2.65% and 8.5%, while for the green spectral range wider ranging values were reported, such as 1.06%, 8.5%, 10.5%, 12.85, and 17.1% …”
Section: Introductionmentioning
confidence: 99%